2014
DOI: 10.1590/2176-9451.19.5.054-066.oar
|View full text |Cite
|
Sign up to set email alerts
|

Facial height in Japanese-Brazilian descendants with normal occlusion

Abstract: OBJECTIVE: The aim of this study was to determine the standards of facial height in 30 young (14-year-old) Japanese-Brazilian descendants with normal occlusion, and assess whether sexual dimorphism is evident. METHODS: The cephalometric measurements used followed the analyses by Wylie-Johnson, Siriwat-Jarabak, Gebeck, Merrifield and Horn. RESULTS: Results showed dimorphism for total anterior facial height (TAFH), lower anterior facial height (LAFH), anterior facial height (AFH), total posterior facial height (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
(42 reference statements)
2
8
0
1
Order By: Relevance
“…The UAFH in normal, horizontal and vertical growth pattern doesn't show significant differences between groups. Study by Wang et al 19 10 showed similar results in Japanese Brazilian descendants. The total anterior facial height also showed similar trend as lower anterior facial height which may be due to the value of lower anterior facial height affecting the total anterior facial height.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The UAFH in normal, horizontal and vertical growth pattern doesn't show significant differences between groups. Study by Wang et al 19 10 showed similar results in Japanese Brazilian descendants. The total anterior facial height also showed similar trend as lower anterior facial height which may be due to the value of lower anterior facial height affecting the total anterior facial height.…”
Section: Discussionsupporting
confidence: 53%
“…In different population, the cephalometric values may vary due to difference in race and ethnicity 9 . Therefore, clinician should have sound knowledge of these variations so that desirable changes can be obtained 10 . Using only one standard for cephalometric analysis is not suitable for all population with different ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out on Japanese-Brazilian descendants it was reported that they also had greater PFH/AFH ratio in comparison to Caucasians. 21 …”
Section: Discussionmentioning
confidence: 99%
“…ditemukan tidak terdapat perbedaan tinggi vertikal wajah yang signifikan pada laki-laki dan perempuan. 22 Tinggi wajah anterior dan posterior lebih besar pada laki-laki dibandingkan perempuan sebesar 3-5% pada awal kelahiran sampai usia 5 tahun selain itu ukuran mandibula pada laki-laki diketahui lebih besar 3-5% pada awal kelahiran. Perbedaan tersebut akan berkurang ketika perempuan telah memasuki masa percepatan pertumbuhan remaja.…”
Section: Pembahasanunclassified